2003
DOI: 10.21000/jasmr03011501
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Simple Scheme to Determine the Chemical Toxicity of Mine Wastes

Abstract: A decision tree that uses simple physical and chemical tests has been developed to determine whether a mine waste poses a toxicity threat to the aquatic environment. For the chemical portion of the tree, leachate tests developed by the US Geological Survey (USGS), the Colorado Division of Minerals and Geology (CDMG), and modified 1311 TCLP test of the EPA have been extensively used. The multi-element power of modern inductively coupled plasma, atomic-emission spectroscopy (ICP-AES) is also a necessary componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…The sediment sampling was performed using the composite method (Smith et al 2000). Three different test methods were used to evaluate the leaching potential of metals: (1) the Toxicity Characteristic Leaching Procedure (TCLP) (EPA Method 1311 1992), (2) the US Geological Survey field leach procedure (USGS-FLT), and the Colorado Division of Minerals and Geology (CDMG) leachate test (Herron et al 1999;Wildeman et al 2003). The metal analysis of water samples and leachate extractions was analyzed using ICP-AES (Perkin Elmer, Optima 3000).…”
Section: Sample Analysismentioning
confidence: 99%
“…The sediment sampling was performed using the composite method (Smith et al 2000). Three different test methods were used to evaluate the leaching potential of metals: (1) the Toxicity Characteristic Leaching Procedure (TCLP) (EPA Method 1311 1992), (2) the US Geological Survey field leach procedure (USGS-FLT), and the Colorado Division of Minerals and Geology (CDMG) leachate test (Herron et al 1999;Wildeman et al 2003). The metal analysis of water samples and leachate extractions was analyzed using ICP-AES (Perkin Elmer, Optima 3000).…”
Section: Sample Analysismentioning
confidence: 99%
“…The first two tests are based on extraction with deionized water and have been developed by Colorado School of Mines (CSM) and the US Geological Survey (USGS) to provide simple and inexpensive methods to assess mine wastes (Wildeman et al 2003(Wildeman et al , 2007. Hageman et al (2005) found that the major source of variation in leaching results arises in the sampling of heterogeneous waste piles, even though the recommended 30 sample composite method of sampling was used (Smith et al 2000).…”
Section: Water Sample Collectionmentioning
confidence: 99%
“…The idea of what should be included in a standard physical assessment of a mine site was developed in conjunction with two regional projects performed by personnel from the CDMG and CSM (Herron et al, 2001;Wildeman et al, 2003). For mine waste piles, a number of on-site observations are made, including the approximate longitude and latitude of the site, the volume of the pile (estimated by measuring the surface exposure using a tape measure and then estimating the depth of the pile), and the presence and hardness of crusts (Herron et al, 2001).…”
Section: Criteria For the Physical Assessmentmentioning
confidence: 99%
“…A preliminary scheme was published three years ago . Since that time, the approach has been further developed and has been used to assess a number of mine sites and two abandoned mining regions (Heflin et al, 2004;Bazin et al, 2003;Wildeman et al, 2003;Moehle et al, 2005;Steele and Wildeman, 2005;Hageman et al, 2005). These projects have reinforced the basic structure of the MWDT that is shown in Figure 1 and have helped to standardize the procedures when the paste pH or leachate pH value of a mine waste material is around the critical value of 5.…”
Section: Introductionmentioning
confidence: 99%